Erik Satie – the ‘progenitor’ of muzak or the precursor of ‘pipedown’ movement? On the concept of musique d’ameublement - Makomaska, Sylwia (Interdisciplinary Studies in Musicology, 2019)
Erik Satie (1866–1925) was a colourful and intriguing artist in the world of Parisian avant-garde. In the turbulent times of the early 20th century he created the concept of musique d’ameublement (‘furniture music’) – a vision of music that did not require attentive listening because it was supposed to play an extravagant role (as it was perceived in that period) of an acoustic background accompanying all everyday events. A change in recording and sound reproduction techniques in the 20th century that led to the ubiquity of music in the contemporary world seems to confirm that Satie’s ‘furniture music’ can be treated as a prophetic idea. However, the problem of how the concept of musique d’ameublement should be interpreted still remains ambiguous. The main aim of the present paper is to discuss the two contrary ways of the interpretation of ‘furniture music’. The first approach assumes that Satie can be treated as ‘the progenitor’ of muzak – a musical genre initially associated with the activities of Muzak company and then gradually identified with any background music provided on a mass scale to the public space. The second approach is an attempt to interpret the concept of musique d’ameublement in a completely different way – as an expression of opposition to an increasingly mechanized Western world dominated by progress and technology, where the role of music boils down only to the function of the acoustic background. Therefore, Satie becomes one of the precursors of the actions taken by the opponents of muzak (e. g. pipedown movements), who seek to eliminate the imposed background music from the public space. The reconstruction of musique d’ameublement (basing, inter alia, on selected source materials) is treated as a starting point for the discussion that leads to the acoustic ecology perspective.